Gender and Racial Differences in Vocational Education, Volume 27, Issue 4. - Rodgers, Yana van der Meulen (International Journal of Manpower., 2006)
The emphasis on vocational education and access to different types of vocational training across demographic groups vary considerably around the world. Gender, racial and ethnic patterns prevail and these set the stage for new research on vocational education and for new policy initiatives that create new opportunities for specialization in vocational training. This e-book covers major topics regarding gender and racial differences in vocational training, and provides perspective for researchers, educators, and policymakers by addressing the imbalances in access to training and types of traini.